Cotton Cost-Return Budget in South Central and Southeast Kansas - Ibendahl, Gregg; O'Brien, Daniel M.; Shoup, Douglas; Duncan, Stewart R.; Haag, Lucas (My University, 2015)
This publication projects a budget that reflects expected income and costs based on production of cotton in south central and southeast Kansas.
MF939_2015_04
Keywords: MF939; Economics; Crops; MF